Functional N‐Formyl Peptide Receptor 2 (FPR2) Antagonists Based on the Ureidopropanamide Scaffold Have Potential To Protect Against Inflammation‐Associated Oxidative Stress. (7th November 2017) - Stama, Madia L.; Lacivita, Enza; Kirpotina, Liliya N.; Niso, Mauro; Perrone, Roberto; Schepetkin, Igor A.; Quinn, Mark T.; Leopoldo, Marcello
Abstract: Formyl peptide receptor 2 (FPR2) is a G protein coupled receptor belonging to the N ‐formyl peptide receptor (FPR) family that plays critical roles in peripheral and brain inflammatory responses. FPR2 has been proposed as a target for the development of drugs that could facilitate the resolution of chronic inflammatory reactions by enhancing endogenous anti‐inflammation systems. Starting from lead compounds previously identified in our laboratories, we designed a new series of ureidopropanamide derivatives with the goal of converting functional activity from agonism into antagonism and to develop new FPR2 antagonists. Although none of the compounds behaved as antagonists, some of the compounds were able to induce receptor desensitization and, thus, functionally behaved as antagonists. Evaluation of these compounds in an in vitro model of neuroinflammation showed that they decreased the production of reactive oxygen species in mouse microglial N9 cells after stimulation with lipopolysaccharide. These FPR2 ligands may protect cells from damage due to inflammation‐associated oxidative stress. Abstract : Stress relief : Prolonged oxidative stress can trigger cell death and has been implicated in the pathogenesis of many neurodegenerative diseases. We report here on a set of ureidopropanamide derivatives that behave as functional antagonists at formyl peptide receptor 2. These compounds decrease the production of reactive oxygen species in lipopolysaccharide‐stimulated mouse microglial N9 cells, an in vitro model of neuroinflammation.